Femmes, genre, migration et mobilités - Catarino, Christine; Morokvasic, Mirjana (Revue européenne des migrations internationales, 2005)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; antiracisme; approches et analyses; cours; discipline; europe; france; féminisme décolonial; inégalités; migration; premier cycle; privilèges; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques

Histoires d’objets - Fassa, Farinaz; Kraus, Cynthia; Malbois, Fabienne (Nouvelles Questions Feministes, 2005)
Number: 1 Publisher: Éditions Antipodes
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; corps; cours; discipline; europe; france; féminisme radical; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis